Evaluation of the ability of milk to act as coating agent in paediatric formulations - Silva, Inês Santos (2020)
Trabalho Final de Mestrado Integrado, Ciências Farmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2019